Impact of left atrial strain on clinical outcomes in patients with permanent pacemaker implantation - Yoshioka, Goro; Yamaguchi, Takanori; Tanaka, Atsushi; Sakai, Hikari; Koyamatsu, Junji; Umeki, Toshiharu; Kaneta, Kohei; Sakamoto, Yoshiko; Kawaguchi, Atsushi; Node, Koichi (ESC Heart Failure, 2024)
Aims This study aimed to investigate the clinical impact of pre‐procedural left atrial strain (LAS) in patients undergoing permanent pacemaker implantation (PPI). Methods and Results This single‐centre retrospective study enrolled 434 patients who were admitted for transvenous PPI between 2010 and 2020. After excluding patients with persistent atrial fibrillation, PPI for complete atrioventricular block, severe valvular disease, history of open‐heart surgery and those without LAS data, 172 patients were analysed. The LAS was measured using commercially available software to calculate the average strain value of the apical four‐ and two‐chamber views before PPI. The primary composite endpoint was hospitalization due to heart failure or cardiovascular death. Cox proportional hazard models were used to evaluate risk factors for the primary composite endpoint. The mean patient age was 78 ± 8 years, and 42% of the patients were men. PPI was performed for sick sinus syndrome in 64% and second‐degree atrioventricular block in 36% of the patients. The pre‐procedure left atrial reservoir strain (LASr) was 28 ± 11%. The median follow‐up period was 4.7 years, and the primary endpoint was observed in 23 (13%) patients. In multivariate Cox proportional risk analysis, LASr was independently associated with the primary composite endpoint (hazard ratio, 1.08 per 1% decrease; 95% confidence interval, 1.02–1.15; P = 0.007). The receiver operating characteristic curve of the LASr for the primary composite endpoint showed a cutoff value of 21% (area under the curve 0.657, P = 0.004). The prognostic impact of LASr was consistent with that of sick sinus syndrome and atrioventricular block. Conclusions A decreased pre‐procedure LASr was associated with long‐term adverse outcomes after PPI use.